How Family Physicians Address Diagnosis and Management of Depression in Palliative Care Patients - Warmenhoven, Franca (American Academy of Family Physicians, 2012)
PURPOSE: Depression is highly prevalent in palliative care patients. In clinical practice, there is concern about both insufficient and excessive diagnosis and treatment of depression. In the Netherlands, family physicians have a central role in delivering palliative care. We explored variation in family physicians’ opinions regarding the recognition, diagnosis, and management of depression in palliative care patients. METHODS: We conducted a focus group study in a sample of family physicians with varied practice locations and varying expertise in palliative care. Transcripts were analyzed independently by 2 researchers using constant comparative analysis in ATLAS.ti. RESULTS: In 4 focus group discussions with 22 family physicians, the physicians described the diagnostic and therapeutic process for depression in palliative care patients as a continuous and overlapping process. Differentiating between normal and abnormal sadness was viewed as challenging. The physicians did not strictly apply criteria of depressive disorder but rather relied on their clinical judgment and strongly considered patients’ context and background factors. They indicated that managing depression in palliative care patients is mainly supportive and nonspecific. Antidepressant drugs were seldom prescribed. The physicians described difficulties in diagnosing and treating depression in palliative care, and gave suggestions to improve management of depression in palliative care patients in primary care. CONCLUSIONS: Family physicians perceive the diagnosis and management of depression in palliative care patients as challenging. They rely on open communication and a long-standing physician-patient relationship in which the patient’s context is of great importance. This approach fits with the patient-centered care that is promoted in primary care.